2000
DOI: 10.1063/1.1290269
|View full text |Cite
|
Sign up to set email alerts
|

AlGaN/GaN metal–oxide–semiconductor heterostructure field-effect transistors on SiC substrates

Abstract: We report on AlGaN/GaN metal–oxide–semiconductor heterostructure field-effect transistors (MOS-HFETs) grown over insulating 4H–SiC substrates. We demonstrate that the dc and microwave performance of the MOS-HFETs is superior to that of conventional AlGaN/GaN HFETs, which points to the high quality of SiO2/AlGaN heterointerface. The MOS-HFETs could operate at positive gate biases as high as +10 V that doubles the channel current as compared to conventional AlGaN/GaN HFETs of a similar design. The gate leakage c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
171
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 326 publications
(178 citation statements)
references
References 8 publications
6
171
0
Order By: Relevance
“…We stress, though, that C-V measurements done only at RT are far from sufficient to characterize wide bandgap GaN and AlGaN interfaces because of the extremely long time constants for electron emission from the deep states at RT ͑approximately 3 months for a level at 1 eV below the conduction band minimum in GaN͒ and an additional factor, such as higher temperature or light, is absolutely necessary to excite carriers from the deep levels. 2,[22][23][24] Therefore, in this work, we performed systematic calculations of theoretical C-V curves from SiN x / Al 0.25 Ga 0.75 N / GaN structures with various thicknesses of SiN x and the AlGaN layer, different densities, and distributions of the states at the SiN x / AlGaN interface at RT, 300°C, or 500°C, taking into account the low rate of electron emission from the deep levels. A parallel shift of the theoretical C-V curves instead of the expected change in their slope was found in the studied devices with a 25-nmthick AlGaN layer at RT and at 300°C when the SiN x / AlGaN interface state density D it ͑E͒ was increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We stress, though, that C-V measurements done only at RT are far from sufficient to characterize wide bandgap GaN and AlGaN interfaces because of the extremely long time constants for electron emission from the deep states at RT ͑approximately 3 months for a level at 1 eV below the conduction band minimum in GaN͒ and an additional factor, such as higher temperature or light, is absolutely necessary to excite carriers from the deep levels. 2,[22][23][24] Therefore, in this work, we performed systematic calculations of theoretical C-V curves from SiN x / Al 0.25 Ga 0.75 N / GaN structures with various thicknesses of SiN x and the AlGaN layer, different densities, and distributions of the states at the SiN x / AlGaN interface at RT, 300°C, or 500°C, taking into account the low rate of electron emission from the deep levels. A parallel shift of the theoretical C-V curves instead of the expected change in their slope was found in the studied devices with a 25-nmthick AlGaN layer at RT and at 300°C when the SiN x / AlGaN interface state density D it ͑E͒ was increased.…”
Section: Introductionmentioning
confidence: 99%
“…While keeping the merits of conventional Schottky-gate-based HFETs, i.e., a high density of two-dimensional electron gas ͑2DEG͒ at the AlGaN/GaN interface, high cutoff and maximum frequencies, and the thermal and chemical stability of AlGaN and GaN, MISHFETs offer many advantages over HFETs, such as lower gate leakage current, higher breakdown voltage, better thermal stability of the gate, mitigation of current collapse, a wider range of gate voltage sweep, and higher maximum drain current and output power. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] These features are crucial for applications in high-power, high-temperature electronics, 7,17 particularly to realize low on-resistance and normally off highpower FETs. 15,18 Although the standard high frequency capacitancevoltage ͑C-V͒ measurement at room temperature ͑RT͒ is usually done on metal/insulator/semiconductor heterostructure ͑MISH͒ capacitors and/or metal/semiconductor heterostructure ͑MSH͒ Schottky diodes before the fabrication and characterization of the MISHFET devices, the C-V data are often used only to estimate the thicknesses of the insulator film and/or the AlGaN layer 1,4,12,16,19 or to calculate the 2DEG density.…”
Section: Introductionmentioning
confidence: 99%
“…Minimizing the impact of vertical leakage paths is crucial for vertical current-flow devices, such as heterojunction bipolar transistors, in which large emitter-collector currents have been observed. 1 Lateral current-flow devices such as heterostructure field-effect transistors 2,3 can also suffer due to gate leakage currents arising from excessively leaky Schottky contacts. However, with an improved understanding of the leakage current mechanisms in electronic devices based on the group-III-nitride material system, 4 -6 rapid progress is currently being made to decrease the off-state leakage current in GaN-based electronic devices, 7,8 which has been a major obstacle to their use in low-noise and low-power circuit applications.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated that the maximum saturation current can be further increased, with no degradation in f T , by using metal-oxide-semiconductor HFET ͑MOSHFET͒ device structures. 2 This allows up to ϩ10 V of gate bias and a maximum current of 1.3 A/mm for a device with a 1.5-m-long gate. Furthermore, a maximum current of more than 5 A from a single-multigate on-wafer MOSH-FET was also measured and reported recently.…”
Section: Mechanism Of Radio-frequency Current Collapse In Gan-algan Fmentioning
confidence: 99%